Dimensionally stable and bioactive membrane for guided bone regeneration: An in vitro study. Issue 3 (7th May 2015) - Rowe, Matthew J.; Kamocki, Krzysztof; Pankajakshan, Divya; Li, Ding; Bruzzaniti, Angela; Thomas, Vinoy; Blanchard, Steve B.; Bottino, Marco C.
Abstract: Composite fibrous electrospun membranes based on poly(dl ‐lactide) (PLA) and poly(ε‐caprolactone) (PCL) were engineered to include borate bioactive glass (BBG) for the potential purposes of guided bone regeneration (GBR). The fibers were characterized using scanning and transmission electron microscopies, which respectively confirmed the submicron fibrous arrangement of the membranes and the successful incorporation of BBG particles. Selected mechanical properties of the membranes were evaluated using the suture pullout test. The addition of BBG at 10 wt % led to similar stiffness, but more importantly, it led to a significantly stronger (2.37 ± 0.51 N mm) membrane when compared with the commercially available Epiguide® (1.06 ± 0.24 N mm) under hydrated conditions. Stability (shrinkage) was determined after incubation in a phosphate buffer solution from 24 h up to 9 days. The dimensional stability of the PLA:PCL‐based membranes with or without BBG incorporation (10.07–16.08%) was similar to that of Epiguide (14.28%). Cell proliferation assays demonstrated a higher rate of preosteoblasts proliferation on BBG‐containing membranes (6.4‐fold) over BBG‐free membranes (4‐ to 5.8‐fold) and EpiGuide (4.5‐fold), following 7 days of in vitro culture. Collectively, our results demonstrated the ability to synthesize, via electrospinning, stable, polymer‐based submicron fibrous BBG‐containing membranes capable of sustaining osteoblastic attachment and proliferation—a promising attribute in GBR. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 594–605, 2016.